Quantitative characterisation of the layered structure within lithium-ion batteries using ultrasonic resonance. (June 2022) - Huang, Ming; Kirkaldy, Niall; Zhao, Yan; Patel, Yatish; Cegla, Frederic; Lan, Bo
Abstract: Lithium-ion batteries (LIBs) are becoming an important energy storage solution to achieve carbon neutrality, but it remains challenging to characterise their internal states for the assurance of performance, durability and safety. This work reports a simple but powerful non-destructive characterisation technique, based on the formation of ultrasonic resonance from the repetitive layers within LIBs. A physical model is developed from the ground up, to interpret the results from standard experimental ultrasonic measurement setups. As output, the method delivers a range of critical pieces of information about the inner structure of LIBs, such as the number of layers, the average thicknesses of electrodes, the image of internal layers, and the states of charge variations across individual layers. This enables the quantitative tracking of internal cell properties, potentially providing new means of quality control during production processes, and tracking the states of health and charge during operation. Highlights: Robust experimental detection of ultrasonic resonance originated from layers of lithium-ion batteries; Established a complete physical model for interpretation of the resonance for quantitative structural information; Demonstrated capabilities in characterising the thickness, the image and the state of charge of individual internal layers.